2016
DOI: 10.1038/ki.2015.319
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization and burden analysis of rare variants in 208 candidate genes suggest they do not play a major role in CAKUT

Abstract: The leading cause of end-stage renal disease in children is attributed to congenital anomalies of the kidney and urinary tract (CAKUT). Familial clustering and mouse models support the presence of monogenic causes. Genetic testing is insufficient as it mainly focuses on HNF1B and PAX2 mutations that are thought to explain CAKUT in 5–15% of patients. To identify novel, potentially pathogenic variants in additional genes, we designed a panel of genes identified from studies on familial forms of isolated or syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 74 publications
6
85
2
2
Order By: Relevance
“…Our result was somewhat in accordance with that of Nicolaou's [32] study and indicated that the proportion of CAKUT/URA cases that followed a recessive model of inheritance was fairly low.…”
Section: Discussionsupporting
confidence: 92%
“…Our result was somewhat in accordance with that of Nicolaou's [32] study and indicated that the proportion of CAKUT/URA cases that followed a recessive model of inheritance was fairly low.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Nicolaou et al [105] recently analyzed, through targeted NGS, 208 candidate genes (selected from studies on familial CAKUT, CAKUT-related multi-organ syndromes, and in vitro and in vivo models) in a phenotypically heterogeneous cohort of 453 CAKUT patients, which comprises the largest set of genes analyzed in a numerous cohort of CAKUT patients. They identified 148 candidate variants in 82 genes in 151 patients but only 5 disease-causing mutations (in HNF1β , PAX2 , SIX5 and UMOD genes) were defined as causal mutations.…”
Section: Genetic Resultsmentioning
confidence: 99%
“…Previous studies on kidney anomalies using next-generation sequencing (NGS) have focused on specific disease entities like nephronophthisis or used broadly defined cohorts of patients with congenital anomalies of the kidney and urinary tract (CAKUT), also including cases with only minor anomalies. [5][6][7] It is estimated that variants in protein coding sequence or copy number variants (CNVs), which likely explain the phenotype, can currently be identified in 10%-16% of CAKUT patients. 8 In this study, we investigate the diagnostic yield of targeted-gene sequencing and whole-exome sequencing in a well-defined cohort of autopsied fetuses with severe prenatally diagnosed bilateral kidney anomalies in which previous genetic analyses have not uncovered an underlying cause; and we correlate our genetic findings with detailed phenotypic information, including post-mortem kidney histology.…”
Section: Introductionmentioning
confidence: 99%